Inflammatory Profile of Th9 Cells and Their Protective Potential in Helminth Infections - Yvanna Louise Di Christine Oliveira; Yrna Lorena Matos de Oliveira; Tatyane Martins Cirilo; Ricardo Toshio Fujiwara; Lilian Lacerda Bueno; Silvio Santana Dolabella (Immuno, 2023)
In terms of the global burden of disease, helminthiasis is the most common infectious disease in the world. In response to the disease, the human host develops an immunological response that occurs predominantly through the action of T helper 2 (Th2) cells and the interleukins IL-4, IL-5 and IL-13. However, other types of Th cells, such as Th9, are also involved in the defense against helminths, with the IL-9 produced by these cells promoting the induction of mastocytosis and the increased production of IgG1 and IgE, in addition to the increase in intestinal contractility that promotes the expulsion of worms. Together, IL-9 and IL-10, which is also produced by Th9, induce a type 2 inflammatory response characterized by the coordinated actions of innate lymphoid cells, mast cells, basophils and other cells that work together toward a single objective: the reduction of the parasitic burden. This review presents the latest findings on Th9 effector mechanisms in helminthic infections.